Continuous crafting of uniform colloidal nanocrystals using an inert-gas-driven microflow reactor. Issue 21 (11th May 2015) - Tang, Hailong; He, Yanjie; Li, Bo; Jung, Jaehan; Zhang, Chuchu; Liu, Xiaobo; Lin, Zhiqun
Abstract : A facile and robust scalable strategy based on an inert-gas-driven microflow reactor was developed for crafting high-quality colloidal nanocrystals. Abstract : Recent research has witnessed rapid advances in synthesis of nanocrystals, which has led to the development of a large variety of approaches for producing nanocrystals with controlled dimensions. However, most of these techniques lack the high-throughput production. Herein, we report on a viable and robust strategy based on an inert-gas-driven microflow reactor for continuous crafting of high-quality colloidal nanocrystals. With the judicious introduction of the inert-gas driven capability, the microflow reactor provides an attractive platform for continuous production of colloidal nanocrystals in large quantities, including easily-oxidized nanocrystals. The as-synthesized nanocrystals possessed a uniform size and shape. Intriguingly, the size of nanocrystals can be effectively tailored by varying the flow rate and the precursor concentration. We envision that the microflow reactor strategy is general and offers easy access to a wide range of scalable nanocrystals for potential applications in sensors, optics, optoelectronics, solar energy conversion, batteries, photocatalysis, and electronic devices.